Analisis Kekuatan Bending Komposit Lamina Serat Ijuk Anyam dan Serat Ijuk Acak bermatriks Polyester - Fatkhurrohman Fatkhurrohman; Ismail Ismail; Ferriawan Yudhanto (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2022)
The current automotive industry uses composite materials as an alternative material to replace metal or plastic, due to the advantages of composite materials that have biodegradable properties and support environmental sustainability. Composite materials can be used as car body protectors, as a protector composite materials must withstand compressive loads. Referring to this, the research will be carried out through flexural testing. Study aim is to analyze variations of fiber volume fraction effect to the flexural strength. Method of making composite materials using hand layup then press mold, variations in fiber volume fraction 25%, 30%, 35%, 40%, and 45%. Flexural testing is carried out according to ASTM D-790. The morphology analysis was also carried out on the fractures of result of flexural test. Flexural testing results show that the highest flexural strength is founded in the fiber volume fraction 50% and the lowest flexural strength is founded in the fiber volume fraction 25%, 724.4 MPa and 435.8 MPa, respectively. A suitable composition in the fiber volume fraction of 40% can produce an optimal bond between the matrix and the fiber. Observing the morphology of the fracture and the cross-section of the fracture flexural testing results, it was found that there were fiber fractures with the characteristics of fiber pullout and delamination in each test specimen.